THE SIGNIFICANCE OF THE SPIRITUAL HERITAGE OF THE ENLIGHTENMENT PEOPLE IN THE EDUCATION OF PRE - SCHOOL STUDENTS TODAY (World Bulletin of Social Sciences, 2024)
In this article, the essence, national and universal importance of learning, restoration and promotion of national heritage among elementary school students, attitude to historical and cultural heritage, the issue of harmony of national and universal values in the educational process that it has a special place discussed. At the same time, it was explained in detail that the importance of the social environment of the Jadidist era in the formation of the educational system for primary school students.
Keywords: Homeland; ignorance; morality; education